Collaborative of Mount Tumpa Forest Park (Tahura) Conservation Area HV People in Manado City using IT Management Based - Pandawa, Roy Marthen; Langkai, Jeane E.; Kairupan, Sisca B. (International Journal of Information Technology and Education, 2022)
Mature this management collaboration (collaborative management) in a area conservation Forest considered suitable and capable for reduce various conflict problems that arise. Type research used is qualitative Study descriptive qualitative, descriptive that is something formula driving problem study for explore or take pictures situation social will researched in a manner thorough, broad and deep. Data collected with technique interviews and observations. Study conducted for Describe, analyze and interpret management collaboration of the Gunung Forest Park Conservation Area (TAHURA) Tumpa HV People in Manado. Nope exist involvement and benefits regularly directly felt by the community is indicator that the management done during this not yet suitable by meaning, purpose, principle as well as meaning conservation source power nature live As impact from centralized management and only emphasize one principle protection already bring impact against area in the form of damage environment in the area Forest Park Conservation (TAHURA) Gunung Tumpa HV People. Required change paradigm management, namely collaboration collaboration Management of the Forest Park Conservation Area (TAHURA) Gunung Tumpa HV People must conducted in a manner participatory through actual and factual involvement to role community and related stakeholders other as partner work government. With refers to existing regulations and policies, agencies technical must transparent in give freedom for Public for To do Conservation Area Management especially in Utilization Blocks.